The Green Tax Revolution - Csaba László (Intereconomics)
Abstract Climate crisis is becoming higher on the agenda of the decision makers of the world. A huge amount of resources have been dedicated to green projects, however far less emphasis has been put on tax policy opportunities. Carbon pricing can increase the burden of CO2 producers, but this does not appear to be enough. We need a Green Tax Reform which focuses on the Pigouvian approach and can correct the distortions of different climate hurting activities. Through tax policy tools, the price structure should be drastically changed and serious incentives should be provided to change the behaviours of the consumers and producers to achieve green policy goals.